BEYOND THE DEGREE: UNDERSTANDING THE HIGH GRADUATE UNEMPLOYMENT RATE IN SOUTH AFRICA – A CASE STUDY ON BACHELOR OF APPLIED SCIENCE IN NATURE CONSERVATION GRADUATES – A CROSS-SECTIONAL STUDY. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
<div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="29529503-4b53-43be-aca3-34c0f4d6ca58" data-message-model-slug="gpt-4o"> Background Graduate unemployment remains a pressing issue in South Africa, even within specialized fields like Nature Conservation. Despite growing environmental concerns and increased demand for conservation professionals, many graduates from the Bachelor of Applied Science in Nature Conservation at Mangosuthu University of Technology (MUT) face difficulties in securing relevant employment. This study investigates the underlying causes of graduate unemployment and explores practical strategies to enhance employability. Methods A mixed-methods, cross-sectional study was conducted to assess employment status, barriers to employment, and potential solutions for improving graduate outcomes. Quantitative data were collected through structured questionnaires administered to 150 graduates from 2018 to 2023, focusing on employment status, skill gaps, and work-integrated learning (WIL) experiences. Qualitative data were obtained through semi-structured interviews with 30 employers from conservation agencies, NGOs, and private companies, and 10 academic staff from MUT, exploring perceptions of curriculum relevance and employability trends. Results The study found that 65% of graduates were unemployed, with 30% searching for employment for over a year. Among those employed, 58% held temporary contracts, and only 22% secured permanent positions. Most respondents (75%) were aged 22–30, with a gender distribution of 56% female and 44% male. Key barriers included a mismatch between academic training and industry expectations, especially in GIS, ecological monitoring, and environmental legislation. 70% of graduates struggled to access WIL placements, while 50% cited financial constraints as a barrier to job relocation. Qualitative findings emphasized the importance of field exposure, entrepreneurial development, and soft skill enhancement. Stakeholders proposed embedding mandatory WIL, offering short certifications, and expanding graduate support services. Conclusion There is a clear gap between academic preparation and labor market expectations. Addressing this requires stronger academic-industry alignment. Recommendation Revise the Nature Conservation curriculum to include practical and technical training aligned with industry needs to improve graduate employability.